2018
DOI: 10.1007/s10518-018-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behaviour of soft clay and its influence on the response of friction pile foundations

Abstract: In recent years, much of the research in geotechnical earthquake engineering has focused on liquefaction of loose, saturated sands and silts. However, the dynamic behaviour of soft, clayey soils and their interaction with pile foundations during the earthquakes have received relatively little attention. In this study, an attempt is made to investigate the dynamic behaviour of soft clay and its interaction with pile foundations during earthquakes using high gravity centrifuge testing. A model single pile and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…In this case, the surrounding soil may undergo large shear strains during earthquake shaking beyond the linear range which makes the accuracy of linear or equivalent linear models at least questionable. In support to the above, recent findings from centrifuge tests on the seismic behavior of soft clays under large intensity levels of input motions ( [15], [16], [17]) revealed attenuation of base acceleration as it propagates through the soil due to the inability of the soft clay to transmit shear stresses close to its limited shear strength. Stiffness degradation with the number of loading cycles has also been observed having a direct impact on the free-field loading imposed on piles [17].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In this case, the surrounding soil may undergo large shear strains during earthquake shaking beyond the linear range which makes the accuracy of linear or equivalent linear models at least questionable. In support to the above, recent findings from centrifuge tests on the seismic behavior of soft clays under large intensity levels of input motions ( [15], [16], [17]) revealed attenuation of base acceleration as it propagates through the soil due to the inability of the soft clay to transmit shear stresses close to its limited shear strength. Stiffness degradation with the number of loading cycles has also been observed having a direct impact on the free-field loading imposed on piles [17].…”
Section: Introductionmentioning
confidence: 61%
“…In support to the above, recent findings from centrifuge tests on the seismic behavior of soft clays under large intensity levels of input motions ( [15], [16], [17]) revealed attenuation of base acceleration as it propagates through the soil due to the inability of the soft clay to transmit shear stresses close to its limited shear strength. Stiffness degradation with the number of loading cycles has also been observed having a direct impact on the free-field loading imposed on piles [17]. Such non-linear behavior of soft clays under seismic action and the associated implication on the selection of a proper constitutive law was examined in [18] for a very soft marine clay which exists at the subsoil of Maliakos Gulf in central Greece.…”
Section: Introductionmentioning
confidence: 61%
“…has shown that the shear modulus values determined during different base excitations for the soil strata in Test-FPC agrees well with the Darendeli ( 2001) modulus reduction curves, especially for the soft clay layer. In addition, Garala and Madabhushi (2019) highlighted the importance of performing nonlinear seismic ground response analysis by accounting cu in the analysis for the sites with soft clays.…”
Section: Ts < Vsmin/(8×fmax)mentioning
confidence: 99%
“…From the perspective of the interaction between homogeneous clay and a pile, Wang and Zhang (2014) conducted centrifuge model tests to study the seismic strengthening mechanism of stabilising piles by assessing the deformation profiles of slopes reinforced by stabilising piles under seismic load. Garala and Madabhushi (2019) studied the interaction between friction piles and soft clay under seismic load in centrifuge model tests. The aforementioned dynamic model tests of slope stabilising piles, and their mechanism of action, are mainly based on the dynamic response characteristics of sand, clay, and other homogeneous slopes; however, there are few studies on the dynamic response of a deposit slope with underlying bedrock and the working mechanism of the coarse-grained rock and soil mixture deposits, thus making it difficult to meet the needs of engineering practice.…”
Section: Introductionmentioning
confidence: 99%